Intracavitary/Interstitial Applicator Plus Distal Parametrial Free Needle Interstitial Brachytherapy in Locally Advanced Cervical Cancer: A Dosimetric Study - Qu, Hong-Da; Han, Dong-Mei; Zhang, Ning; Mao, Zhuang; Cheng, Guang-Hui (Frontiers in Oncology, 2021)
PURPOSE: To explore the dosimetric advantage of combining intracavitary/interstitial applicator with distal parametrial free needle interstitial brachytherapy (IC/IS+ISBT DP) based on MRI for locally advanced cervical cancer. METHODS AND MATERIALS: 77 IC/IS+ISBT DP treatment plans were developed for 34 locally advanced cervical cancer patients between June 2016 and January 2020. We removed the free needles and devised a new IC/ISBT treatment plan according to the same principle. We then compared the dosimetric differences of D90, D98, V100 , V150, V200 for HR-CTV (high-risk clinical target volume), D90 for IR-CTV (Intermediate risk-CTV) and D2cc for OARs (organs at risk) between the two group plans for the same patient, and the paired T test was performed in parallel. Further,the dosage differences between the two group plans under different parametrial extension widths (the maximum distance of HR-CTV from the vertical direction of the uterine tandem at coronal position) were compared.The survival rate was calculated by the Kaplan-Meier method. Prognostic factors for overall survival (OS) and progression-free survival (PFS) were determined by Cox regression method.RTOG/EORTC criteria are used to grade toxicities. RESULTS: A total of 297 free needles were used,their weight ratio was 15.8%±0.11,and the mean insertion depth was 6.52cm±2.8cm.D90, D98, V100 for HR-CTV and D90 for IR-CTV for IC/IS+ISBT DP were significantly higher than IC/ISBT for which free needles were removed (p＜0.05). And the V200 for HR-CTV and D2cc for bladder, rectum and sigmoid were decreased (p＜0.05). When the parametrial extension widths were greater than 3cm, the HR-CTV D90 and the D2CC for rectum, bladder and sigmoid colon for IC/IS-ISBT DP were advantageous compared to IC/ISBT (p＜0.05).The 2-yr OS,PFS and local control rate (LC) were 82.06% ,66.6% and 92.9%,respectively.Parametrial extension widths was the only statistically prognostic factors for PFS (p = 0.002) on univariate analysis.No grade 3 or 4 Treatment-related toxicities were observed. CONCLUSION: Our institutional experiences showed that IC/IS+ISBT DP is an effective treatment for cervical cancer patients with distal parametrial extension.IC/IS-ISBT DP had dosage advantage and clinical feasibility in locally advanced cervical cancer with distal parametrial extension when the parametrial extension widths were greater than 3cm.